A Gene-Expression Predictor for Efficacy of Induction Chemotherapy in Locoregionally Advanced Nasopharyngeal Carcinoma - Lei, Yuan; Li, Ying-Qin; Jiang, Wei; Hong, Xiao-Hong; Ge, Wen-Xiu; Zhang, Yuan; Hu, Wei-Han; Wang, Ya-Qin; Liang, Ye-Lin; Li, Jun-Yan; Cho, William C S; Yun, Jing-Ping; et al. (JNCI : Journal of the National Cancer Institute, 2021)
Abstract Background Induction chemotherapy (IC) followed by concurrent chemoradiotherapy is the mainstay treatment for patients with locoregionally advanced nasopharyngeal carcinoma. However, some patients obtain little benefit and experience unnecessary toxicities from IC. We intended to develop a gene-expression signature that can identify beneficiaries of IC. Methods We screened chemosensitivity-related genes by comparing gene-expression profiles of patients with short-term tumor response or nonresponse to IC (n = 95) using microarray analysis. Chemosensitivity-related genes were quantified by digital expression profiling in a training cohort (n = 342) to obtain a gene signature. We then validated this gene signature in the clinical trial cohort (n = 187) and an external independent cohort (n = 240). Tests of statistical significance are 2-sided. Results We identified 43 chemosensitivity-related genes associated with the short-term tumor response to IC. In the training cohort, a 6-gene signature was developed that was highly accurate at predicting the short-term tumor response to IC (area under the curve [AUC] = 0.87, sensitivity = 87.5%, specificity = 75.6%). We further found that IC conferred failure-free survival benefits only in patients in the benefit group (hazard ratio [HR] = 0.54, 95% confidence interval [CI] = 0.34 to 0.87; P = .01) and not on those in the no-benefit group (HR = 1.25, 95% CI = 0.62 to 2.51; P = .53). In the clinical trial cohort, the 6-gene signature was also highly accurate at predicting the tumor response (AUC = 0.82, sensitivity = 87.5%, specificity = 71.8%) and indicated failure-free survival benefits. In the external independent cohort, similar results were observed. Conclusions The 6-gene signature can help select beneficiaries of IC and lay a foundation for a more individualized therapeutic strategy for locoregionally advanced nasopharyngeal carcinoma patients.